Exploring Female Teachers' Experiences in Facing Gender Discrimination in the Workplace: A Phenomenological Perspective - Hikmah, Arina Nur; Kusmaryani, Rosita Endang; Herwin, Herwin; Qureshi, Muhammad Saifullah (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
Gender discrimination in the workplace remains a persistent issue in the education sector, where female teachers continue to experience unequal treatment that affects their professional roles and personal well-being. This study aims to explore female teachers’ lived experiences of gender discrimination, focusing on how they perceive and navigate gender bias, the impacts of discrimination on their professional and personal lives, and the coping strategies they employ. Using a phenomenological approach, this study applied Interpretative Phenomenological Analysis (IPA) to in-depth data collected through semi-structured interviews with three female teachers. The findings reveal multiple dimensions of gender discrimination in the school environment, including its underlying causes, psychoemotional impacts, limited institutional support, the role of the work environment, participants’ expectations for change, and strategies used to cope with discriminatory practices. From the perspective of positive psychology, the results indicate that gender discrimination undermines subjective well-being and constrains the development of individual potential. Female teachers largely rely on personal resilience and peer support in the absence of systematic organizational protection. The novelty of this study lies in its phenomenological examination of gender discrimination by foregrounding female teachers’ subjective experiences within the educational workplace, thereby offering a holistic understanding of discrimination that integrates structural, emotional, and coping dimensions. The study underscores the urgent need for changes in institutional mindsets, organizational structures, and workplace cultures, as well as the implementation of gender-sensitive policies and practices to foster inclusive, supportive, and gender-equitable educational environments.